Neuromuscular training improves movement competency and physical performance measures in 11-13-year-old female netball athletes - Hopper, A.; Haff, E. E.; Barley, O. R.; Joyce, C.; Lloyd, R. S.; Haff, G. G. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to examine the effects of a neuromuscular training (NMT) program on movement competency and measures of physical performance in youth female netball players. It was hypothesized that significant improvements would be found in movement competency and physical performance measures after the intervention. Twenty-three junior female netball players (age, 12.17 ± 0.94 years; height, 1.63 ± 0.08 m; weight, 51.81 ± 8.45 kg) completed a test battery before and after a 6-week training intervention. Thirteen of these athletes underwent 6 weeks of NMT, which incorporated plyometrics and resistance training. Trained athletes showed significant improvements in 20-m sprint time, 505 agility time, countermovement jump height, and peak power (p = 0.05, g > 0.8). In addition, trained athletes significantly improved their score in the Netball Movement Screening Tool (NMST) (p < 0.05, g > -1.30); while the athletes also demonstrated increased reach in the anterior and posteromedial directions for the right leg and left leg, and in the posterolateral direction for the left leg only in the Star Excursion Balance Test (SEBT) (p < 0.05, g > -0.03). Control subjects did not exhibit any significant changes during the 6-week period. Significant negative correlations were found between improved score on the NMST and decreased 5-, 10-, and 20-m sprint time, and 505 change of direction time (r > 0.4, p = 0.05). Results of the study affirm the hypothesis that a 6-week NMT intervention can improve performance and movement competency in youth netball players.